Factors Associated with 60-Day Readmission Following Cytoreduction and Hyperthermic Intraperitoneal Chemotherapy - Kelly, Kaitlyn J.; Cajas, Luis; Baumgartner, Joel M.; Lowy, Andrew M. (Annals of surgical oncology, 2018)
Introduction Readmission rates following surgery are subject to scrutiny in efforts to control health care costs. This study was designed to define the 60-day readmission rate following cytoreduction and HIPEC at a high-volume center and to identify factors associated with readmission. Methods Patients who underwent complete cytoreduction and HIPEC at a single institution from August 2007 through June 2014 were identified from a prospectively maintained database. Multiple preoperative and operative factors were analyzed for their ability to predict 60-day readmission following surgery. Results A total of 250 patients were identified. Forty patients (17%) experienced readmission within 60 days of surgery. The most common reasons for readmission were ileus/dehydration (12, 31%), deep space infection (8, 21%), and DVT/PE (6, 15%). Initial postoperative length of stay was longer for patients readmitted within 60 days (median 12 vs. 9 days, p = 0.013). Of categorical variables analyzed, including gender, histology, HIPEC agent, intraoperative transfusion, and individual procedures performed during cytoreduction, adjuvant systemic therapy, and postoperative morbidity, only Charlson comorbidity index CCI (odds ratio (OR) = 3.80 [1.68–8.60]) and stoma creation (OR = 6.04 [1.56–12.14]) were associated with 60-day readmission. Conclusions Few measurable variables are associated with readmission following cytoreduction and HIPEC. Patients with high CCI and those with stomas created at the time of CRS/HIPEC may be at increased risk of readmission within 60 days. Earlier or more frequent follow-up for high-risk patients should be considered as a strategy to reduce readmissions.